A sustainable Arctic: Making hard decisions. Issue 1 (1st January 2018) - Trump, Benjamin D.; Kadenic, Maja; Linkov, Igor
ABSTRACT: The Arctic is experiencing substantial increases in human activity in areas ranging from fossil fuel and mineral extraction to transport along Arctic waterways. Such actions may yield new sources of economic benefits and further objectives to promote national defense, yet they may also generate potential risks to the Arctic environment. As such, concerns from various stakeholders have been raised regarding how to make Arctic operations better meet sustainability goals and balance defense and economic objectives with environmental degradation. This article describes how decision analytical tools, such as multicriteria decision analysis (MCDA), may help identify policies and project proposals that minimize the potential for environmental degradation within a framework of maximizing economic, industrial, and defense objectives. Specifically, MCDA conducts value tradeoffs to assess the utility of various decision alternatives against disparate criteria; for this case, this includes the evaluation of Arctic operation sustainability. This article demonstrates through an example of industrial mining in Greenland how MCDA might serve as a tool to guide uncertain decisions for various Arctic projects, and potentially indicate opportunities to structure such projects to provide greater sustainability for their longer-term operations.